2014
DOI: 10.4236/health.2014.616245
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Measuring Axillary Temperature Using Mercury in Glass Thermometers in Children under Five Years: A Cross Sectional Observational Study

Abstract: Background: Measuring axillary temperature with mercury in glass thermometers is continued in clinical practice though there are many limitations. This is mainly due to convenience and cost. This study was conducted to ascertain the accuracy of measuring axillary temperature with mercury thermometers in preschool children. Methods: Axillary temperature was measured in 250 preschool children using standardized mercury thermometers. Time taken to record the final temperature and its correlates were assessed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In 78.3% of cases, a stable rectal temperature was obtained at two minutes. These data were in accordance with the studies conducted by Chaturvedi et al [28] and Nichols et al [30] [32] with an allowable error of ±0.1˚C. Other studies used several observers and one minute intervals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In 78.3% of cases, a stable rectal temperature was obtained at two minutes. These data were in accordance with the studies conducted by Chaturvedi et al [28] and Nichols et al [30] [32] with an allowable error of ±0.1˚C. Other studies used several observers and one minute intervals.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found there was no correlation between the time taken to reach a stable rectal temperature and age, body weight, gender, or final rectal temperature. In contrast, Perera et al [32] found that axillary temperature measurement time in children was related to age, body mass index, and final axillary temperature. These findings suggested that the time required for an accurate rectal temperature measurement was short, and that rectal temperature measurement was not influenced by patient demographic factors.…”
Section: Discussionmentioning
confidence: 87%
“…In this study the bilateral differences of mass screening body core temperature methods were assessed; all have been able of estimating an intrinsic error, as demonstrated by previous research (Fernandes et al 2016, Towey et al 2017. The axilla differences can be explained by the time of exposure as suggested by Perera et al (2014); the tympanic membranes are in line with what was demonstrated by Childs et al (1999), despite having a larger sample, and can be influenced by the amount of wax in the ear channel. The authors of the current research disagree with the previous study in their recommendation to always use the same site for consecutive assessments; perhaps a second complimentary method is more adequate than relying in this method bias.…”
Section: Discussionmentioning
confidence: 56%
“…The gold standards are the oesophagal and rectal temperatures; however, these sites cause discomfort for most people and are not easy to access (Moran and Mendal 2002). Over time, other sites have been proposed and introduced in daily practice such as axillary thermometers, initially of mercury and later digital; but, due to unreliability in their readings, which are dependent on the placement time, they have since been replaced by tympanic membrane thermometers (Perera et al 2014). Childs et al (1999) demonstrated that, using tympanic membrane thermometers, there is a potential a measurement error from one recording to the next of about 0.1 °C to 0.2 °C.…”
Section: Introductionmentioning
confidence: 99%